2017
DOI: 10.1016/j.matdes.2017.02.085
|View full text |Cite
|
Sign up to set email alerts
|

Tunable bandgap and spin-orbit coupling by composition control of MoS 2 and MoO x (x = 2 and 3) thin film compounds

Abstract: We report on composition controlled MoS 2 and MoO x (x=2 and 3) compounds electrodeposited on Flourine dopped Tin Oxide (FTO) substrate. It was observed that the relative content has systematic electrical and optical changes for different thicknesses of layers ranging from ≈20 to 540 nm. Optical and electrical bandgaps reveals a tuneable behavior by controlling the relative content of compounds as well as a sharp transition from p to n-type of semiconductivity. Moreover, spin-orbit interaction of Mo 3d doublet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 32 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…In contrast to that in case of MoSO-RGO the current can pass from two possible channels: 1-perpendicular with following succession: from MoSO to the FTO then from FTO to MoSO and from MoSO to RGO or 2-pass horizontally from MoSO to the interface with RGO and finally with a perpendicular current to Gr. The inset shows I-V characteristic curve of thicker MoSO layer (which we expect to be N-type semiconductor) in the MoSO-RGO mode where clearly confirms our previous work [16]. This behavior shows a significant shift of the Fermi level toward conduction band.…”
Section: I-v Characteristics and Optical Propertiessupporting
confidence: 86%
See 2 more Smart Citations
“…In contrast to that in case of MoSO-RGO the current can pass from two possible channels: 1-perpendicular with following succession: from MoSO to the FTO then from FTO to MoSO and from MoSO to RGO or 2-pass horizontally from MoSO to the interface with RGO and finally with a perpendicular current to Gr. The inset shows I-V characteristic curve of thicker MoSO layer (which we expect to be N-type semiconductor) in the MoSO-RGO mode where clearly confirms our previous work [16]. This behavior shows a significant shift of the Fermi level toward conduction band.…”
Section: I-v Characteristics and Optical Propertiessupporting
confidence: 86%
“…In this research, we report on electrical and optical properties of the MoSO/RGO electrodeposited on Fluorine doped tin oxide (FTO) substrate. In the previous report [16], it was observed that the oxygen content has systematic change for different thicknesses ranging from 20 to 540 nm. Optical and electrical bandgaps reveals a tunable behavior by controlling the relative content of compounds as well as a sharp transition from p to n-type of semi conductivity.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Preparation of the Solution Containing MoS 4 2− : For preparation of the solution, similar to our previous work, we used an aqueous bath containing 0.39 M Na 2 MoO 4 · 2H 2 O and 0.88 M Na 2 S · 5H 2 O with adjusted pH to 7 by adding sulfuric acid. Fresh solutions were used in BPE of the heterostructures.…”
Section: Methodsmentioning
confidence: 99%
“…This is a result of the higher ratio of stoichiometric trioxide phases with wide absorption edge, and this trend is in good agreement with that from previous studies. 27,28 Increased transmittance was observed after the post-annealing process in the case of the MoO X with O 2 /Ar ratio of 6/14 sccm, along with a slight increase in band-gap. This might be due to the Burstein-Moss shift 29,30 caused by the Fermi-level shift to higher energy in a heavily doped semiconductor.…”
Section: Optical Propertiesmentioning
confidence: 97%